Islamic perspective exploratory review : creative multimedia technology as an innovative tool for Da'Wah dissemination - Mohamad Fauzan Noordin; Irma Pammusu; Shuhada Sulong; Nur Nazihah Rahim (Universiti Malaysia Kelantan, 2015)
Multimedia is defined as the combination of several communications media such as audio, video, text, etc to produce the creative content artificial artifact. Nowadays, people live in the super corridor highway information communication technology era where they cannot imagine themselves without this technology advancement. It can be a benefit or a disaster depending on people who decide on the direction of their use. It depends on how we look into multiple perpectives of the technology. The computer technology and ICTare not just enable to enhance the dissemination of knowledge but they also provide the platforms to develop better knowledge of society around the world effectively. Thus, this research paper is meant to conduct a critical review on Creative Multimedia from Islamic perspective and the elements in Multimedia such as virtual reality, database and privacy issues. Several evidences form the Holy Book (The Quran) which is also used as reference in this exploratory review. This research paper uses to support arguments presented Holy Book (The Quran) and the practices of Prophet Muhammad (peace be upon Him).